What must be added to 3x -7 to make x2 + 4x -1?

x^2 + x + 6 must be added 3x - 7 to make x^2 + 4x - 1 (x^2 + 4x - 1) - (3x - 7) = (x^2 + 4x - 1) + (-3x + 7) = x^2 + x + 6; (3x - 7) + (x^2 + x + 6) = x^2 + 4x - 1

Question

Asked 3/1/2013 10:50:33 AM

Updated 11/17/2014 6:02:51 AM

1 Answer/Comment

Edited by andrewpallarca [11/17/2014 6:02:51 AM]

Rating

3

x^2 + x + 6 must be added 3x - 7 to make x^2 + 4x - 1

(x^2 + 4x - 1) - (3x - 7)

= (x^2 + 4x - 1) + (-3x + 7)

= x^2 + x + 6;

(3x - 7) + (x^2 + x + 6)

= x^2 + 4x - 1

(x^2 + 4x - 1) - (3x - 7)

= (x^2 + 4x - 1) + (-3x + 7)

= x^2 + x + 6;

(3x - 7) + (x^2 + x + 6)

= x^2 + 4x - 1

Added 11/17/2014 5:54:00 AM

This answer has been confirmed as correct and helpful.

What does tragedy mean? **Weegy:** Tragedy is a form of drama based on human suffering that invokes in its audience an accompanying catharsis or pleasure in the viewing. ] (More)

Question

Expert Answered

Updated 10/12/2014 10:01:29 AM

0 Answers/Comments

27,084,506

questions answered

There are no comments.